Gambaran Asupan Cairan Berdasarkan Status Gizi Pada Remaja Putri Di Pondok Pesantren Darul Aman Gombara Makassar - Aulia Maghfirah; Rahayu Indriasari; veni Hadju; Sabaria Manti; Healthy Hidayanty (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Introduction: Teenage girls belong to the nutritional vulnerable group. Nutritional intake in adolescent age is crucial to support their physical growth. Nutritional problems that occur in adolescents are generally caused by a factor that is a less precise diet related to fluid intake that affects the state of nutritional status, especially in teenagers who attend school like in islamic boarding school. Purpose: This study aims to know the description of fluid intake based on adolescent nutritional status in Darul Aman Gombara islamic boarding school. Materials and methods: the type of this study is survey design. Sample This study of 96 teenagers using total sampling. Retrieval of intake data using 24 hours recall method for 3 days IE day on school day and public holiday. Determination of nutritional status obtained from parameters Z-Score IMT/U. Processing and analysis of data on this research using SPSS. Result : The results of the analysis are known that the intake of adolescent drinks with skinny nutritional status as much as 100% are in the category of less fluid intake. For normal nutritional status 87,5% of teenagers are in the category of intake of less drinks and other 12,5% insufficient. And fat nutritional status 91,7% of respondents were in the category of less fluid intake and another 8,3% was sufficient. While the nutritional status of respondents is normal as much as 83.3%, fat nutrition status as much as 12.5%, and lean nutritional status as much as 4.2%. Conclusion: The Most intake of adolescent fluid are lacking in the status of Fat nutrition, and the nutritional status of respondents is a nutritional status of good/normal.